Potret Kehidupan Sosial dan Ekonomi keluarga Tenaga Kerja Wanita Asal Kota Dumai - Rahmah Husna Yana; Irma Juraida; Triyanto Triyanto; Arfriani Maifizar (Jurnal Community, 2019)
AbstractThis research aims to determine the extent of the social and economic life portrait of the family of Women Workers (TKW) from Dumai city who work in Malaysia, TKW in this study is limited to TKWs who work in the domestic realm. The location of the study was carried out in Pangkalan Sesai Village, West Dumai District, with the selection of information carried out deliberately on 4 TKW families. Data collection techniques using observation, interviews, and documentation. Data analysis uses descriptive qualitative analysis through the stages of reduction, presentation of data, and conclusions. The results showed that there was a change in the socioeconomic life of TKW families from the city of Dumai, the change came from the remittances sent by TKW where the money was used for social and economic life of the family left behind.Keywords: Social-Economy life, Family, TKW